A Q-Methodological Study: Which Factors are Considered to be the Most Impactful for the Academic Success of Black-African Caribbean Males? - Robinson, Tavelah (2024)
The present study focuses on the consistent academic disparities experienced by Black African Caribbean (BAC) children and young people (CYP) within the UK educational landscape, emphasising their persistent underperformance on average, when compared to other ethnicities (Bowe, 2015; Demie & Mclean, 2017; Roberts & Bolton, 2020). Recent evidence from the Department for Education (DfE; Strand, 2021) on Attainment 8 scores signifies limited progress in tackling such inequalities, highlighting the imminent need for further investigation into the distinct educational shortcomings faced by BAC CYP and the necessity to develop bespoke interventions tailored to subgroup differences (Demie & Mclean, 2017; Roberts & Bolton, 2020; Commission on Racial and Ethnic Disparities, Education and Training, 2021). Bronfenbrenner’s ecological systems theory is used as a framework for understanding the complex layers of influence affecting the attainment of BAC CYP within schools, specifically in relation to systemic biases such as institutional racism (Bronfenbrenner, 1977; Nation et al., 2020). This framework sheds light on the interwoven systems within the educational environment and stresses the importance of developing targeted interventions to address the underlying causes of academic disparities (McLaughlin & Talbert, 2006; Valencia, 2010).